EFFECTS OF STUMP CHARACTERISTICS AND SOIL NUTRIENTS ON STUMP RESPROUTING OF Schima superba - Zhao, Houben (2018)
Schima superba is a widely distributed and broadly planted broadleaf tree in southern China. Information regarding the probability of stump resprouting, characteristics of the growth of resprouts and their influencing factors after disturbance is lacking. In this study, plant survey plots were established in fertile and barren soil conditions one month after a severe ice-snow storm disaster and the resprouting investigations were conducted four years after the treatment. The species showed a rather high (87.8% in total) resprouting probability and independent of stump diameter and soil nutrient condition but positively affected by stump height. Stumps in fertile soil can generate more resprouts than in barren soil and there is no influence in the subsequent resprouts survival and growth. Stump diameter has no influence on the number of resprouts per stump generated, but facilitated the survival and growth of resprouts. Stump height had a positive influence on resprouts number per stump generated and a negative influence on resprouts growth, but had no significant influence on resprouts survival rate and dominant resprouts growth. We recommend conducting a harvest of S. superba at large diameter and <30 cm aboveground level (traditional method) to obtain a balance between economic efficiency and regeneration. Fertilization immediately following logging or disturbance and artificial resprouts thinning is not recommended for this species.